PENGARUH WORKLOAD DAN JOB INSECURITY TERHADAP WORK FATIGUE - Nurul Mardiana; Fachrudy Asj’ari (J-MACC, 2022)
This study aims to analyze the effect of Workload and Job Insecurity on Work Fatigue MTs Teachers at the Al-Ihsan Krian Sidoarjo Foundation. The approach used is descriptive quantitative as well as the population & sample used by a number of 53 employees. According to the statistical results, the t-count results of Workload 2.821 & a significance of 0.007 <0.05. Obtained t-count Job Insecurity 2.194 & a significance of 0.033 <0.05. The f-count was 8,643 & a significance of 0.001 <0.05. This means that the t-test & f-test prove that there is a significant and positive effect of Workload and Job Insecurity on the Work Fatigue of MTs Teachers at the Al-Ihsan Krian Sidoarjo Foundation.